Pengembangan Bahan Ajar Tematik Berbasis Kearifan Lokal Kalimantan Barat Pada Kelas III Tema 3 SD/MI Tahun 2019/2020 - Maha Lastasa Buju Basafpipana Habaridota (Universitas Kanjuruhan Malang, 2022)
The purpose of this research is to develop thematic textbooks that are not in accordance with the real condition in west kalimantan. This research uses the Research and Development using quantitative and qualitative approaches. The results of the study can be concluded that: The results of the cover and content design, the linguist's assessment, the material assessment an average of 4.66, percentage of agreement (PoA) of 92.00% in a very good criteria, eligible for use in third grade of elementary school. The results of the study have an impact on students and more interesting in understanding teaching material books based on local wisdom, this is because the books are adapted to local culture, especially Pontianak, West Kalimantan